A Case Report of Myelopathy Following Heroin Overdose in a Child. (28th July 2021) - Melikishvili, Ana; Patel, Bijal; Hasbani, Daphne M.; Carvalho, Karen S.
Neurologic complications secondary to heroin abuse in the adult population have been widely described in the literature. With the recent opioid epidemic and increasing rates of heroin abuse in adolescents, pediatricians are now encountering the diagnostic and management challenge of similar complications in children. We report a case of a 16-year-old girl who presented with complete paraplegia after a heroin overdose. Spinal magnetic resonance imaging showed diffuse thoracic spinal cord abnormalities. She rapidly recovered after high dose intravenous corticosteroids and, upon hospital discharge 2 weeks later, required minimal assistance with ambulation. This case represents the youngest patient reported with the rare complication of myelopathy associated with heroin use.